Penerapan Model Pembelajaran Discovery Learning Berbasis Media IT Untuk Meningkatkan Hasil Belajar PAI Siswa Di SMP N 1 Jujuhan, Kecamatan Jujuhan Ilir Kabupaten Bungo Provinsi Jambi - Devi Novita Sari; Zulfani Sesmiarni; Arifmiboy Arifmiboy; Junaidi Junaidi (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
The background of this research is on the subject of Islamic Religious Education that teachers still rarely use the discovery learning learning model in learning so that students are not effective in participating in the learning process and when students are given assignments by the teacher, almost all students in class VII cannot do the assignments given, so symptoms or phenomena are found, especially in subjects Islamic Religious Education, namely the learning outcomes of class VII students are still relatively low and have not yet reached the minimum completeness criteria (KKM) set at SMP N 1 JUJUHAN, namely 75. The purpose of this research is to find out whether student learning outcomes have increased by applying the discovery learning model to the eyes Islamic religious education lessons. This research is a Class Action Research (CAR) which is carried out in two cycles, with each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this study were class VII students of SMP N 1 JUJUHAN, Jujuhan Ilir District, Bungo Regency, Jambi, even semester of the 2021/2022 academic year, which consisted of 15 male students and 5 female students. In collecting data the author uses the method of observation, learning achievement tests, and documentation. The data analysis technique used is descriptive data analysis, where the data is analyzed qualitatively and quantitatively in the form of percentages. The results of this study are that the application of discovery learning learning models can improve student learning outcomes in the material Al-Khulafaur Ar Rasyidun The Successor of the Struggle of the Prophet Muhammad. Before the action, it was known that 8 students had completed with 40% classical completeness, in cycle I, 12 students had completed with 60% classical completeness, in cycle II, 18 students had completed with 90% classical completeness. Thus it can be concluded that by applying the discovery learning model it can improve student PAI results at SMP N 1 JUJUHAN.